(x-1)+(2x+3)+(2x+3)=180

Simple and best practice solution for (x-1)+(2x+3)+(2x+3)=180 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (x-1)+(2x+3)+(2x+3)=180 equation:


Simplifying
(x + -1) + (2x + 3) + (2x + 3) = 180

Reorder the terms:
(-1 + x) + (2x + 3) + (2x + 3) = 180

Remove parenthesis around (-1 + x)
-1 + x + (2x + 3) + (2x + 3) = 180

Reorder the terms:
-1 + x + (3 + 2x) + (2x + 3) = 180

Remove parenthesis around (3 + 2x)
-1 + x + 3 + 2x + (2x + 3) = 180

Reorder the terms:
-1 + x + 3 + 2x + (3 + 2x) = 180

Remove parenthesis around (3 + 2x)
-1 + x + 3 + 2x + 3 + 2x = 180

Reorder the terms:
-1 + 3 + 3 + x + 2x + 2x = 180

Combine like terms: -1 + 3 = 2
2 + 3 + x + 2x + 2x = 180

Combine like terms: 2 + 3 = 5
5 + x + 2x + 2x = 180

Combine like terms: x + 2x = 3x
5 + 3x + 2x = 180

Combine like terms: 3x + 2x = 5x
5 + 5x = 180

Solving
5 + 5x = 180

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-5' to each side of the equation.
5 + -5 + 5x = 180 + -5

Combine like terms: 5 + -5 = 0
0 + 5x = 180 + -5
5x = 180 + -5

Combine like terms: 180 + -5 = 175
5x = 175

Divide each side by '5'.
x = 35

Simplifying
x = 35

See similar equations:

| 9=87/3/4 | | 15x-.75=13x-.50 | | 87=3/4/9 | | 15x/2+19=12x+7/2 | | 14/19/11 | | 9x^4-10x^2+1=0 | | 1(t-3)+7t=4(2t+4)-13 | | x=0.40(x+15) | | 76c=828 | | y-5=-1/8x | | 7x+3y=5 | | 196*47/49*1/16 | | p-r=c | | 20+15x/2=21 | | 2(5-n)=-25 | | 5/7x=30 | | x+2x+2=10 | | 5/2+5/2y=2y-4 | | 6-2(3x-5)=-8 | | 14+8x=55 | | w=-r | | 12x-170=4x-10 | | 11x-2(x-7)=9(x+1)+7 | | a^2-13a+22=0 | | 7t=4*49 | | 5-9x=-173 | | x+2x+1=10 | | (n-5)*9=54 | | 9(x-1)-3=6x+3(-3+x) | | 47-4x=14x+21 | | 28x+91=220 | | 13-9x=68-4x |

Equations solver categories